A framework and simulation engine for studying artificial life - James, H.A.; Scogings, C.; Hawick, K.A. (Massey University, 2004)
The area of computer-generated artificial life-forms is a relatively recent field of inter-disciplinary study that involves mathematical modelling, physical intuition and ideas from chemistry and biology and computational science. Although the attribution of “life” to non biological systems is still controversial, several groups agree that certain emergent properties can be ascribed to computer simulated systems that can be constructed to “live” in a simulated environment. In this paper we discuss some of the issues and infrastructure necessary to construct a simulation laboratory for the study of computer generated artificial life-forms. We review possible technologies and present some preliminary studies based around simple models.
Keywords: Artificial life; Simulation engine; Computer-generated artificial life; Simulated environment